MAPPING TREND IMPLEMENTASI STRATEGI PROMOSI DESA WISATA KEMBANGARUM TURI SLEMAN YOGYAKARTA - Yulianto, Atun; Mayasari, Citra Unik (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2018)
Kabupaten Sleman has many tourist attraction objects that can be used as tourist destinations for anyone. The attraction of this city includes the panorama of nature, history, museums, culture, ancient relics, culinary and tourist villages. The number of tourist villages in Sleman regency is in accordance with the data of the Sleman Regency Culture and Tourism Office (Fauzy & Putra, 2015), as many as 38 tourist villages. The tourism village management base generally involves many parties, including by empowering local communities as local communities who play an active role in managing and developing tourism villages. However, according to (Damanik, 2013), "The weak point of the local community in managing tourism services is networking and promotion capabilities". The success of the tourism village manager in influencing the perception of visitors with their promotional tools can trigger the decision to visit. In this case, the right selection of promotional tools (promotional mix) is very important in addition to attracting tourists, as well as the progress of the tourism village itself. The number of tourist visits is a measure of the success of managers in developing the right promotional strategies. The constraints faced by the manager of the tourist village of Kembangarum Turi Sleman Yogyakarta are related to the weak network for promotion. A promotion has been carried out both conventionally and through internet media but not yet interactive, thus reducing the understanding of the wider community of the existence of the Kembangarum tourism village. The research method used is a qualitative descriptive method assisted with quantitative data tabulation. The results of the study with relevant data that is read indicate the trend of a shift in the implementation of promotional strategies with media that are conventional to modern with the help of information technology, especially the internet since the period 2015/2016. The conclusions of this study include: it is known that the most optimal use of conventional promotional media is by providing brochures, and word of mouth information. Whereas in the span of the last three years the promotion has focused more on online promotional media through social networks that have been owned by the tourism village manager of Kembangarum. This shift in promotion strategy proved to have an impact on increasing the number of tourist village visitors, especially in the period of 2016/2017 where this promotional strategy began to be implemented since the period of 2015/2016. Keywords: Promotion, Strategy,Trend Mapping